Movement-related beta ERD and ERS abnormalities in neuropsychiatric disorders - Peter, Jaime; Ferraioli, Francesca; Mathew, Dave; George, Shaina; Chan, Cameron; Alalade, Tomisin; Salcedo, Sheilla A.; Saed, Shannon; Tatti, Elisa; Quartarone, Angelo; Ghilardi, M. Felice (Frontiers in Neuroscience, 2022)
Movement-related oscillations in the beta range (from 13 to 30 Hz) have been observed over sensorimotor areas with power decrease (i.e. event-related desynchronization, ERD) during motor planning and execution followed by an increase (i.e. event-related synchronization, ERS) after the movement’s end. These phenomena occur during active, passive, imaged, and observed movements. Several electrophysiology studies have used beta ERD and ERS as functional indices of sensorimotor integrity, primarily in diseases affecting the motor system. Recent literature also highlights other characteristics of beta ERD and ERS, implying their role in processes not strictly related to motor function. Here we review studies about movement-related ERD and ERS in diseases characterized by motor dysfunction, including Parkinson’s disease, dystonia, stroke, amyotrophic lateral sclerosis, cerebral palsy, and multiple sclerosis. We also review changes of beta ERD and ERS reported in physiological aging, Alzheimer’s disease, and schizophrenia, three conditions without overt motor symptoms. The review of these works shows that ERD and ERS abnormalities are present across the spectrum of the examined pathologies as well as development and aging. They further suggest that cognition and movement are tightly related processes that may share common mechanisms regulated by beta modulation. Future studies with a multimodal approach are warranted to understand not only the specific topographical dynamics of movement-related beta modulation but also the general meaning of beta frequency changes occurring in relation to movement and cognitive processes at large. Such an approach will provide the foundation to devise and implement novel therapeutic approaches to neuropsychiatric disorders.